2019
DOI: 10.1177/0886260519869693
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment, Stress, and Depressive Symptoms Among Female Survivors of Intimate Partner Violence Attending Personal Empowerment Programs

Abstract: Intimate partner violence (IPV) affects one in three women and can have long-lasting psychological effects, with abuse survivors typically exhibiting elevated stress and depressive symptoms. However, women with greater personal empowerment resources (i.e., self-care, agency, self-efficacy) and who practice relaxation techniques generally exhibit lower stress and depressive symptoms. The present study investigated the effectiveness of Personal Empowerment Programs (PEP) and practicing relaxation techniques in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
(62 reference statements)
2
13
0
Order By: Relevance
“…self-care, agency, and self-efficacy), and practiced relaxation techniques, tended to show less stress and depressive symptoms. 45 Our results were consistent with the results of Chehrazi et al who confirmed the direct impact of spiritual well-being (as a main component of self-care) on health-promoting behaviors. 11 Another study confirmed that religiosity was significantly associated with health promotion as a personal factor and interpersonal influence.…”
Section: Discussionsupporting
confidence: 93%
“…self-care, agency, and self-efficacy), and practiced relaxation techniques, tended to show less stress and depressive symptoms. 45 Our results were consistent with the results of Chehrazi et al who confirmed the direct impact of spiritual well-being (as a main component of self-care) on health-promoting behaviors. 11 Another study confirmed that religiosity was significantly associated with health promotion as a personal factor and interpersonal influence.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies documented that the prevalence of stress and PPD was higher among mothers who experienced sexual domestic violence than mothers who did not; 40 , 46 however, corroborating a previous study, 40 the mediating effect of stress in the association of sexual domestic violence with PPD symptoms was not identified in this study. In fact, this study found no significant relationship between sexual domestic violence victimisation and PPD.…”
Section: Discussionsupporting
confidence: 81%
“…personal victimisation, household/property victimisation, cyberbullying and physical/sexual ex-partner abuse) and psychological health outcomes, such as self-reported mental health and life satisfaction. It is well documented that being the victim of domestic violence is related to increased experiences of stress 40 , 41 and stress-related mental health problems such as depression. 16 , 42 Higher perceived stress is negatively associated with self-efficacy, 43 coping resources and associated behaviours, 44 all of which influence future vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Routine screening of depression is also needed among female outpatients to better protect their mental health as they develop. Future interventions among abused Thai women may want to utilize an empowerment approach (e.g., Garcia et al, 2019) to decrease their likelihood of experiencing stress and their subsequent risk for depression. Such programs should focus not only on stress reduction but could also focus on social supports as needed.…”
Section: Discussionmentioning
confidence: 99%